Space, time, & stuff - Arntzenius, Frank (Oxford : Oxford University Press, 2012)
Frank Arntzenius presents a series of radical ideas about the structure of space and time, and establishes a new metaphysical position which holds that the fundamental structure of the physical world is purely geometrical structure.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Ontology; Space and time; Geometry in nature